2001
DOI: 10.1046/j.1365-2095.2001.00154.x
|View full text |Cite
|
Sign up to set email alerts
|

The effects of krill hydrolysate-supplemented soya-bean based diets on the growth, colouration, amino and fatty acid profiles of juvenile American lobster,Homarus americanus

Abstract: The feasibility of soya-based diets for pounded American lobster, Homarus americanus, was investigated using diets (40% protein) of low-fat soya-bean meal (SBM) containing various proportions of freeze-dried krill hydrolysate (FDKH) at 0, 12.5, 25, 50, 75, and 100% of dietary protein, in a 60-day trial using stage 5 juveniles. Diets of fresh bluemussel, Mytilus edulis, and a diet of 100% of protein from ®sh meal (FM), approximating the industry diet of ®sh, were included for comparison. Speci®c growth rates (S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 17 publications
0
9
0
1
Order By: Relevance
“…2006; Gaber 2005). However, krill is most commonly used as a high‐value additive to aquaculture feeds (Floreto et al. 2001) rather than the primary ingredient.…”
Section: Development Of Productsmentioning
confidence: 99%
See 1 more Smart Citation
“…2006; Gaber 2005). However, krill is most commonly used as a high‐value additive to aquaculture feeds (Floreto et al. 2001) rather than the primary ingredient.…”
Section: Development Of Productsmentioning
confidence: 99%
“…Experiments have shown that krill meal has a nutritional value equal to, or surpassing, that of regular fish meals when used as a substitute in the diets of various farmed species, including Atlantic cod, Atlantic salmon and Pacific white shrimp (Yoshitomi et al 2007;Karlsen et al 2006;Opstad et al 2006;Gaber 2005). However, krill is most commonly used as a high-value additive to aquaculture feeds (Floreto et al 2001) rather than the primary ingredient. Given proven benefits of utilization of krill meal and oils [the addition of fish oil to meals is used to boost Omega-3 content of farmed species (IFFO, 2008)] in fish meals and the decline of traditional sources of these meals and oils, krill is being examined as a means to satisfy demand in a market niche that will be under increasing pressure as traditional fish stocks continue to decline.…”
Section: Development Of Productsmentioning
confidence: 99%
“…Diets containing protein hydrolysate have been previously shown to improve growth in several larval fish species (Carvalho et al, 1997;Ovissipour et al, 2014;Srichanun et al, 2014), as well as in juvenile (Floreto et al, 2001;Hernández and Olvera-Novoa, 2011) and adult crustaceans (Cordova-Murueta and Garcia-Carreno, 2002;Nguyen et al, 2012). The growth benefits of hydrolysed protein have largely been attributed to the increased abundance of short-chain peptides and FAAs released by the enzymatic process (Aksnes et al, 2006;Bui et al, 2014;Zheng et al, 2012).…”
Section: Discussionmentioning
confidence: 96%
“…; Hertrampf & Piedad‐Pascual ; Floreto et al . ; Córdova‐Murueta & García‐Carreño ; Quinto et al . )).…”
Section: Traditional Sourcesunclassified
“…The protein hydrolysates could enhance the protein utilisation. Litopenaeus vannamei and Homarus americanus fed with diets supplemented with fish protein hydrolysates show increased growth (Anggawati et al 1990;Hertrampf & Piedad-Pascual 2000;Floreto et al 2001;C ordova-Murueta & Garc ıa-Carreño 2002;Quinto et al 2018)). Hern andez et al (2011) have found that, via lactic acid fermentation, tuna by-product protein hydrolysate (TBPH) improves the digestibility and amino acid profile of porcine meal-based diets, and thus enhances the growth response of L. vannamei.…”
Section: Animal Sourcesmentioning
confidence: 99%